Accessibility to family planning services among pantawid pamilyang Pilipino program beneficiaries - Ortega, Ma. Christina B. (San Carlos City, Pangasinan : [s.n.], 2018)
This study aimed to determine the accessibility to family planning services among beneficiaries. Specifically, it determined the demographic profile of the respondents as to: age, number of children, educational attainment, family monthly income, source of income; the extent of the accessibility to the family planning services among beneficiaries along: information dissemination, availability of commodities, and competence of FP Providers; the problems encountered by the beneficiaries in terms of their accessibility to FP services; and the significant relationship between the demographic profile and the extent of their accessibility to FP services, and the enhancement program formulated to improve their accessibility to the FP services.
Bibliography: pages 108-113.
CHED-La Union
Keywords: Birth control -- Social services